2021
DOI: 10.1108/wje-10-2020-0518
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation system for finding improved coworking area based on intelligent information technologies

Abstract: Purpose The purpose of this study is to make the implementation of a recommended Web service that allows one to formalize the search for a suitable coworking according to individual preferences as a decision-making task, as well as find a coworking area in an optimized setting for both the individual employee and those who carry out collective professional activities from a large number of alternatives in a shorter time. Design/methodology/approach In the implemented system of each place category in coworkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Traditional recommendation systems often build a model to minimize the distance between the quantitative data of users' real behavior and the prediction results [26]. The optimization process is realized by loss function.…”
Section: Attention Mechanism Of Fusion Path and Design Of Recommendat...mentioning
confidence: 99%
“…Traditional recommendation systems often build a model to minimize the distance between the quantitative data of users' real behavior and the prediction results [26]. The optimization process is realized by loss function.…”
Section: Attention Mechanism Of Fusion Path and Design Of Recommendat...mentioning
confidence: 99%
“…Mariotti et al (2021) agree that coworking spaces are mainly an urban phenomenon. A recent study by Kotciuba et al (2021) concluded that a presence of coworking environments in a selected metropolitan area correlates with lowered labour management costs for companies that tend to track and cater to their employees' personal and work-related needs. Still, the evidence by Mariotti et al (2021) suggests that coworking environments in rural and peripheral areas have steadily grown, mainly as the share of teleworkers outside of metropolitan areas primarily increased.…”
Section: The Pre-pandemic Workplace For 'Working Alone Together'mentioning
confidence: 99%